Roger’s syndrome presenting with stroke - Kataria, Bhavya; Patra, Bijoy; Chumber, Shishir; Vani, Kavita (International Journal of Contemporary Pediatrics, 2023)
Rogers syndrome (Thiamine responsive megaloblastic anaemia-TRMA) occurs due to defect in the SLC19A2 gene. SLC19A2 and SLC19A3 genes encode THTR1 and 2 respectively, which are thiamine transporter proteins. The SLC19A2 gene is expressed in the inner ear cells, β-islet cells, and hematopoietic stem cells; consequently, the typical clinical trial of TRMA is diabetes, TRMA, and sensorineural hearing loss. This syndrome, eponymously called Roger’s syndrome is rare. Mode of inheritance of TRMA is autosomal recessive. Clinical presentation as recurrent stroke is extremely rare. We present a case of a five-year-old boy who had recurrent large artery territory cerebral infarcts, with no other identifiable underlying cause of stroke. During current admission, no underlying etiology could be identified for cerebral infarct. On workup, a preliminary diagnosis of TRMA was made and thiamine supplementation was instituted. Gene analysis confirmed the diagnosis. The child was a product of non-consanguineous marriage. There was history of early childhood demise of two older siblings within five years of age due to diabetic ketoacidosis (DKA). TRMA is a rare autosomal recessive syndrome that manifests as a typical triad with diabetes, hearing loss and megaloblastic anaemia. The treatment is with high dose thiamine supplementation that can alleviate symptoms of diabetes and megaloblastic anaemia. Onset and progression of hearing loss may be delayed with treatment. Some cases may present with recurrent stroke as in the proband.